2010
DOI: 10.1104/pp.110.162792
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Abscisic Acid as a Key Switch for Natural Variation in Flooding-Induced Shoot Elongation    

Abstract: Elongation of leaves and stem is a key trait for survival of terrestrial plants during shallow but prolonged floods that completely submerge the shoot. However, natural floods at different locations vary strongly in duration and depth, and, therefore, populations from these locations are subjected to different selection pressure, leading to intraspecific variation. Here, we identified the signal transduction component that causes response variation in shoot elongation among two accessions of the wetland plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 58 publications
0
40
0
1
Order By: Relevance
“…In the case of deepwater rice, the decline in ABA augments GA-mediated internode elongation and ethylene-dependent adventitious root formation during submergence (Hoffmann-Benning and Kende, 1992;Steffens et al, 2006). Recently, it was reported that modulation of internal ABA levels is a key determinant in the rate of underwater petiole elongation in submergence-tolerant Rumex palustris ecotypes, allowing escape of leaves from floodwaters (Chen et al, 2010). It appears that submergence-induced ABA degradation is a prerequisite for escape of submergence through rapid shoot elongation.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of deepwater rice, the decline in ABA augments GA-mediated internode elongation and ethylene-dependent adventitious root formation during submergence (Hoffmann-Benning and Kende, 1992;Steffens et al, 2006). Recently, it was reported that modulation of internal ABA levels is a key determinant in the rate of underwater petiole elongation in submergence-tolerant Rumex palustris ecotypes, allowing escape of leaves from floodwaters (Chen et al, 2010). It appears that submergence-induced ABA degradation is a prerequisite for escape of submergence through rapid shoot elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Underwater escape by Rumex palustris and quiescence of Rumex acetosa are conferred by distinctions in the elongation of leaf petioles involving the same ethylene, ABA, and GA hierarchy established for rice (Benschop et al, 2005;Bailey-Serres and Voesenek, 2008). For example, ABA insensitivity corresponded to greater underwater petiole elongation in R. palustris ecotypes (Chen et al, 2010). In this species, elongation growth toward the water surface is complemented by upward hyponastic curvature of the petiole.…”
Section: Quiescence and Escape In Other Speciesmentioning
confidence: 99%
“…However, when subjected to extended periods of flooding and the water column is relatively shallow, it may be more beneficial to the plant to undergo rapid shoot elongation to escape submersion. Some species rapidly elongate their stems or petioles keeping leaves above the water surface, facilitating gas exchange and light interception (Voesenek et al 2004;Kolb & Joly 2009;Manzur et al 2009;Chen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation that occurs in these areas is subject to flooding in the rainy season, when the water table reaches or almost reaches the surface. Flooding may induce multiple physiological dysfunctions in plants, such as inhibition of photosynthesis and transport of carbohydrates, reduced absorption of nutrients (due to root death and loss of mycorrhiza in plants with these associations) and hormonal changes such as increase in ethylene (He et al 1996;Kozlowski 1997) and abscisic acid (ABA) (Benschop et al 2005;Chen et al 2010) concentrations or decrease in cytokinin biosynthesis (Zhang et al 2000). Flooding also induces premature senescence resulting in leaf chlorosis, necrosis and leaf loss (Zhang et al 2000).…”
Section: Introductionmentioning
confidence: 99%